2009
DOI: 10.1063/1.3081184
|View full text |Cite
|
Sign up to set email alerts
|

First principles elaboration of low band gap ladder-type polymers

Abstract: Ladder-type polymers, obtained by small modifications of the atomic structure of ladder-type polythiophene, are studied using density-functional theory calculations. Within the local-density and GW approximations, it is found that upon a simple substitution of the sulfur atoms by nitrogen and boron atoms, the band structure of the resulting polymer exhibits band overlap between the occupied and the unoccupied states. However, the three-parameter Becke hybrid functional predicts these polymers to be small band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Specifically, the width of a particular electronic band reflects its orbital interactions along the polymer chain, with wide bands denoting delocalization and narrow bands corresponding to localization/small orbital overlap. For each of the different polymers, we found that their electronic band structures showed they were all semiconductors with a direct band gap at the Γ symmetry point (it should be noted, however, that not all one-dimensional polymers have direct band gaps; for example, several ladder-type polymers such as the fused polyborole structures in ref have indirect band gaps). Figure displays the band structures for polypyrrole, polycyclopentadiene, and their benzannulated versions.…”
Section: Resultsmentioning
confidence: 94%
“…Specifically, the width of a particular electronic band reflects its orbital interactions along the polymer chain, with wide bands denoting delocalization and narrow bands corresponding to localization/small orbital overlap. For each of the different polymers, we found that their electronic band structures showed they were all semiconductors with a direct band gap at the Γ symmetry point (it should be noted, however, that not all one-dimensional polymers have direct band gaps; for example, several ladder-type polymers such as the fused polyborole structures in ref have indirect band gaps). Figure displays the band structures for polypyrrole, polycyclopentadiene, and their benzannulated versions.…”
Section: Resultsmentioning
confidence: 94%
“…Figure 1 shows that each unit cell of graphene FLP nanoribbon 2a has the molecular formula C 4 B 2 N 2 H 4 . One unit cell of 2a may be formed from zigzag graphene (polyacene 28,46 ) nanoribbon 4 (unit cell formula C 8 H 4 ), and boron nitride nanoribbon 5 (unit cell formula B 4 N 4 H 4 ) as (2)…”
Section: ■ Resultsmentioning
confidence: 99%
“…Figure shows that each unit cell of graphene FLP nanoribbon 2a has the molecular formula C 4 B 2 N 2 H 4 . One unit cell of 2a may be formed from zigzag graphene (polyacene , ) nanoribbon 4 (unit cell formula C 8 H 4 ), and boron nitride nanoribbon 5 (unit cell formula B 4 N 4 H 4 ) as 1 2 normalC 8 normalH 4 + 1 2 normalB 4 normalN 4 normalH 4 normalC 4 normalB 2 normalN 2 normalH 4 (Calculations use the unit cells in Figure .) M06/6-311G(2d,2p)//HSE06/6-31G(d) calculations predict that this isodesmic reaction has an energy change Δ E = +96.3 kcal/mol per unit cell (+0.95 kcal/g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contracted Gaussian basis sets have successfully been used to study the interaction between polymers and metals [32][33]. These contracted Gaussian basis sets on an imposed periodic boundary conditions were also succesfully utilized by [34][35] in their ab initio study of polypyrrole and ladder-polypyrrole. It was revealed that the 6-31G basis set suited well for polypyrrole with periodic boundary conditions.…”
Section: Computational Detailsmentioning
confidence: 99%